Mobile learning in Indonesian higher education: quantitative analysis of EFL integration, challenges, and impact - Fauziah, Arifah; Kim, Hyeonjin (Intelektual Pustaka Media Utama, 2026)
This quantitative research investigated the integration of mobile learning in teaching English as a foreign language (EFL) within Indonesian higher education. This research adopts a two-phase data collection approach, using a structured questionnaire distributed to 134 lecturers from 86 universities and follow-up interviews with 11 selected lecturers. In analyzing this research, Statistical Package for Social Sciences (SPSS) version 26.0 used to provide comprehensive insights into lecturers’ experiences, availability, effectiveness of mobile learning, and adequacy of facilities and content design. The results reveal a general positive attitude towards mobile learning integration (mean score 4.29 out of 5), with particular challenges identified, such as minimal classroom facilities and difficulties in content design. The implications show the importance of combining technology with teaching and support, while the conclusion points out readiness, benefits, and challenges in EFL instruction. At the same time, the conclusion highlights readiness, benefits, and challenges, serving as a guide for further exploration and development in EFL instruction. The importance of this research is intended in delivering and analyzing the development of technology used, readiness of lecturers and facilities challenging, and aligning technology with teaching practice. The study’s limitations encompass potential over-reliance on self-reported data and limited geographical and institutional scope, with recommendations for future mixed-method research, expansion, collaboration, and continuous training and investment in classroom infrastructure.